Suppression of biofilm formation on selected plant pathogenic fungi using tea tree oil - Andrew, Bernice (2017)
Fusarium solani, F. oxysporum, Phytophthora palmivora and Pyricularia oryzae are best examples of plant pathogenic fungi that have the ability to cause enormous economic losses on crops worldwide annually. Formation of biofilm is one of the survival strategies for bacteria and fungi to adapt to their surrounding environment, especially when exposed to the hostile environment. Thus, the objective of this study was to assess efficacy of tea tree oil to suppress formation of biofilm in fungi. Fusarium solani, F. oxysporum and P. oryzae were cultured in PDA medium while P. palmivora was cultured in CMA medium. Microtiter plate method and poisoned food technique were used in this study. It was revealed that tea tree oil (TTO) showed 100% mycelial inhibition on F. oxysporum and F. solani at concentration of 1000 ppm. TTO was found to be less effective against P. oryzae and P. palmivora. For 96-well plates, TTO was able to suppress the growth of biofilm at concentration of 50,000 ppm and 100,000 ppm. Biofilm quantification was determined based on the reduction of XTT (a tetrazolium salt) by metabolically active fungal biofilm cells.